A prática jornalística em áreas de guerra: uma experiência brasileira na cobertura do conflito na Líbia - Lopes, Rodrigo Guimarães (Universidade do Vale do Rio dos Sinos, 2016)
This MA paper analyses the journalistic activity in war zones. For that matter, we've tried to know the track of the war correspondents activity in the last decades from the 19th century to the first 15 years of the present century, identifying tensions and possible mutations in these professional's profile as well as their routine focusing on the experience of Brazilian journalists while covering conflicts. As a Case Study, we analyzed the experience of four Brazilian reporters; O Estado de São Paulo's Andrei Netto, Folha de São Paulo's Samy Adghirni, O Globo's Deborah Berlinck, and Zero Hora's Humberto Trezzi, who worked as war correspondents in Libya's war in 2011. After thorough interviews with these professionals, who are reference where they work, we aimed to tension their empirical experience based on theories produced by thinkers who are of fundamental importance to Journalism. For analyzing it we created categories: How to Become a War Correspondent; The Practice of Exercising Journalistic Production; and Reflections that Go Beyond Practice. In order to answer the question "how does the war affect the journalistic practice", we think on journalism key-subjects in war zones: differences between local and war coverage; the journalist/source relation and the interview; technology; censorship, self-censorship and embedded question; violence and the putting life at risk.
Keywords: Jornalismo internacional; Correspondente de guerra; Líbia; Entrevista; International journalism; War correspondente; Libya; Interview; ACCNPQ::Ciências Sociais Aplicadas::Comunicação